The development of communication networks of pre-service teachers on a school-led and university-led programme of initial teacher education in England. (2020) - Brouwer, Jasperina; Downey, Christopher; Bokhove, Christian
Highlights: Communication networks among trainee teachers become less dense during their training programme. There is limited boundary-spanning between trainees on university- and school-led programmes. Friendship is an early-stage predictor in the development of communication networks. Advice-seeking is a late-stage predictor in the development of communication networks. Communication around peer-support becomes more mutual among mathematics trainees over time. Abstract: This study examines the communication networks of 77 pre-service teachers in mathematics and science on university and school-led programmes in England. Communication as an indicator for establishing contact is considered as the starting point of building social capital among peers. Communication, advice-seeking and friendship network data were collected over four time-points during each programme. The descriptive results suggest limited boundary-spanning between the university and school-led programme types. Longitudinal modelling in RSIENA showed that friendship is a significant early-stage predictor of development of communication networks. By the end of the programme advice-seeking becomes a significant predictor of network development. Neither interpersonal trust, nor perceived self-efficacy were found to be consistent predictors of change in pre-service teacher communication networks.